PENELITIAN PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA DAN DAMPAKNYA TERHADAP LINGKUNGAN - Martin Djamin (Jurnal Teknologi Lingkungan, 2010)
Indonesia through government programmes and private sector activities. An assessment on performance of photovoltaic systems and study of their impacts was established in Kolaka, South-east Sulawesi. At the moment there are 2270 solar home systems (SHS) in this location. During the research and study, there are 9 data loggers have been installed in nine solar home systems in 4 villages of Kolaka. These data loggers were used to monitor and measure some parameters such as solar insolation , VBattery,VLoad, ILoad, IModule, and room temperature. Besides performance data collection above, a quantitative research method was done to explore the quality of life of rural and remotepeoples. 175 questionnaires were used to collect the data from households in 4 villages Polinggona, Popalia, Petudua dan Pewisoa Jaya. This paper will discuss resuts of the measurement of solar home systems, the impact on daily life of villagers and global and local environmental impact of the use of solar home systems.Kata Kunci: PLTS, data-logger, alat pengontrol baterai